Communism - Connolly, Sean J. (Systems of government, 2017)
"Different countries are governed in different ways. Communism is a way of governing a country and its people. The basis of this type of government is the idea that one person is not more important than any other and all citizens work for the benefit of everyone, not just for themselves This book offers a detailed and non-judgemental look at specific countries that are governed in this way. It looks at how communism becomes established, problems and successes that it may encounter and what the future may hold for communism. Part of the Systems of Government series, this balanced book places Communism within a wider world context and looks at the effect this type of government has on its citizens, wealth and industry. "-- Publisher description